Geographic Information System For Infrastructure Damage Handling at Perumdam Tirta Anom - Nurdin, Arif Muhamad (IJISTECH (International Journal of Information System and Technology), 2023)
Perumdam Tirta Anom Banjar city has services to meet the needs of clean water and drinking water for the people of Banjar City. In meeting the needs of clean water Perumdam Tirta Anom has several water treatmen infrastructure, piping, reservoir, pipes and office buildings. Perumdam Tirta Anom Banjar City has the responsibility to handle infrastructure damage based on reports of damage from the community as well as on schedule of periodic maintenance of infrastructure. Monitoring of Perumdam Tirta Anom infrastructure is conducted based on monthly report and grouping of location is still in general in Banjar City area only, so that there are constraints in the accuracy of handling damage. Head of Distribution Section requires a system that can monitor all activities handling infrastructure damage, and assist Head of Sub Division of Planning in determining the main priority of handling infrastructure damage. The proposed solution based on the problems that have been described is building a geographic information system that handles damaged infrastructure of Perumdam Tirta Anom Banjar City. The software development analysis approach used is object-oriented analysis, and geographic information system is built on the website, and for the determination of the main priority of handling infrastructure damage using TOPSIS method.